Diatomáceas (diatomeae): descritores paleoambientais em lagoas do pantana Brasileiro - Nardelli, Margaret Seghetto (2019)
General abstract: The Brazilian Pantanal is considered a green complex of utmost importance due to its potential of natural resources, in addition to the still unknown rich biodiversity. However, even it is considered a World Natural Heritage, it is continually threatened due to an intense antropic action. Thus, in order to bring forth information to support plans and development actions, a study of the structure of diatom communities in surface sediments was carried out. A total of three ponds were sampled in February 2015, at the end of the rainy season. Ferradura Pond (FP) is connected to Cuiabá River, Burro Pond (BP) connected to the São Lourenço River, and Caracará (CP) connected to the Paraguay River. Physical-chemical parameters of water were obtained with the aid of multiparameter probe. Similarly, for biotic analysis, collections in the surface sediment were carried out with Ekman environmental sampler. Concomitantly, surface water samples were collected for chemical analysis of phosphorus, nitrogen and chlorophyll a. The diatom analysis was carried out in permanent blades, with a count of 400 valves, to check the relative density. The attributes that characterize diatom communities have been described such as habitat type, ecology and geographic distribution. Differences among averages by ANOVA and f test were verified for both abiotic (physical-chemical) and determined biotic parameters (species frequency). Pearson's linear analysis was also carried out with species that showed abundance superior to 5%. So, a multivariate statistical analysis was carried out to deal with multiple variables, biological (diatom distribution), chemical and physical, and to classify the results obtained with canonical correspondence analysis (CCA). Indexes and other measures of structure were used to evaluate the community diversity. Student's t-Test was used to compare Shannon-Wiener (H') diversity indexes for the three studied ponds to evaluate if there is a significant difference with confidence interval permutation methods. As a result of flora of Mato Grosso, a total of 119 diatom taxa belongs to 31 genera and 11 orders were reported. Nearly 67% of taxa (79) are distributed in four major genera, which are: Eunotia Ehrenberg (39 taxa), Pinnularia Ehrenberg (18 taxa), Aulacoseira Thwaites (14 taxa) and Gomphonema Ehrenberg (08 taxa). Therefore, the remaining 27 genera have only 1 to 3 taxa, 16 are less than 1% of relative density. Three species are the first citation for Brazil, Eunotia curtiraphe Metzeltin e Lange-Bertalot, Eunotia manfredii Lange-Bertalot, Neidium amphigomphus (Ehr.) Pfitzer, and 81 species are the first citation for Mato Grosso. The greatest numerical richness was found out the Ferradura pond, with 31 genera and 81 taxa, while the Caracará and Burro ponds presented a same diversity of genera (22), but with greater richness in taxa for Caracará (77 taxa) when compared to Burro pond (71 taxa). There was no dominance of species, and the three ponds presented low uniformity, with emphasis on Burro pond that showed the lowest numerical richness, but the greatest diversity in relation to the uniformity. Due to the marshland being an acidic environment, there was a greater species richness of Eunotia Ehrenberg, being the acidophilic characteristic determinant of this genus. It can also be analyzed that a slight increase in trophic level generated an increase in the abundance of Aulacoseira Thwaites.